(untitled) (Scientific journal of the Fergana State University, 2024)
The article describes the scientific and pedagogical foundations of pedagogical diagnostics, control and evaluation of future teachers of fine arts in the process of their professional and methodological training. By means of diagnostics of students, a model was developed for assessing their educational opportunities, features of knowledge and qualification testing, professional and methodological training. Also, as a result of training based on educational technologies, methods of creating opportunities for the growth of knowledge from general and special disciplines are highlighted.